La sabiduría del taita: Chinolope y Lezama Lima - Gema Areta Marigó (Caravelle)
In this paper we analyze the collaboration and complicity existing between Chinolope’s “fulgurant bull’s-eye” and Lezama Lima’s literary fullness when he comments his friend’s photographic imagination concerning sugar mills. It’s the testimony of a splitting that will be published in 1987 under the heading Temporada en el ingenio, thus revealing opposite aspects and resistances.